The Preparation of Tin Oxide Film Heat Mirrors by A Sol Gel Process - Jongjit Hirunlabh; Sarayuth Lorsrichandr; Krissanapong Kirtikara; Ralph D. Pynn (ASEAN Journal on Science and Technology for Development, 2000)
The Preparation of Tin Oxide Film Heat Mirrors by A Sol Gel Process